Chemistry and biological activities of acetogenins from Annonaceae species - Cave, Andre (Malaysian Journal of Science (MJS), 2000)
A brief review on the chemical aspects and biological activity of acetogenins isolated from Annonaceae species which includes their detection, purification and structural identification, is presented.